A Novel Flexible Electrochemical Molecular Imprinted Sensor for the Determination of GABA in Serum of Depressed Mice. Issue 1 (1st January 2023) - Li, Yuanyuan; Wei, Hong; Chen, Yan; Ma, Jing; Zhang-Peng, Xinru; Li, Wen; Hu, Fangdi
Abstract : The content of γ -aminobutyric acid (GABA) in human serum has been proved to be closely related to depression, so the rapid, sensitive, highly selective and accurate determination of GABA is of great significance for the objective diagnosis of depression. In this study, a molecularly imprinted electrochemical sensor based on high-performance magnetically functionalized reduced graphene oxide (MRGO) was constructed for the sensitive detection of GABA in the serum of depressed mice. Using MRGO modified the flexible electrode (ITO-PET), 2, 4-dinitrofluorobenzene derivative of GABA as the template and pyrrole with self-polymerization effect as the functional monomer and cross-linking agent, the molecularly imprinted sensor MIP/MRGO/ITO-PET was successfully constructed by simple electropolymerization and stirring elution. Under the optimal construction process, the sensor realized the accurate detection of GABA in the range of 250 pM ∼ 100 μ M, and the detection limit was as low as 1.25 × 10 −10 M (S/N = 3). The simultaneous possession of high sensitivity and selectivity, good stability, repeatability and reproducibility enables this sensor to be successfully applicable for the determination of GABA in mice serum. The results showed that the sensor is expected to provide a basis for objective diagnosis of depression in clinic.